Mind[full]ness : mindful dining experience - Quek, Joanne Poh Hoon (2016)
In the age of advanced technology, the introduction of personal mobile smart devices has become a huge contributing factor to a modern man’s multitasking habits. Doing multiple tasks at a time is a norm in today’s culture: texting while walking; replying emails in between an work assignment; or even illegally calling someone while driving. The constant need for attention from multiple tasks pulls one away from focusing solely on the experience of the main current task, leading to an overwhelmed mind and mindlessness during the main task. This project explores the concept of mindfulness, specifically during meal time, in hope to calm our mind and enhance our dining experience.